Substance P/Neurokinin 1 and Trigeminal System: A Possible Link to the Pathogenesis in Sudden Perinatal Deaths - Mehboob, Riffat (Frontiers in Neurology, 2017)
Sudden demise of a healthy fetus or a neonate is a very tragic episode in the life of parents. These deaths have been a mystery since ages but still remains unexplained. This review proposes the involvement of trigeminal nerve, its neurotransmitter Substance P (SP) and its receptor Neurokinin 1 (NK1R) in regulation of respiratory rhythm in fetuses and newborns. Anomalies and immaturity of neuroregulator neuronal systems such as trigeminal system in medulla oblongata of brainstem may provide a possible mechanism of sudden perinatal deaths. Vulnerable infants are born with respiratory centre immaturity which in combination with any stressor such as cold, hypoxia, smoking may lead to cessation of breathing and ventilatory response. Substance P/NK1R may be involved in regulating the ventilatory control in neonates while it is decreased in fetal and adult life in humans and any alterations from these may lead to irreversible sleep apnea and fatal breathing, ultimately sudden death. This review summarizes the studies performed to highlight the expression of SP or NK1R in sudden perinatal deaths; proposes the involvement of trigeminal ganglion along with it’s nerve and SP/NK1R expression alteration as one of the possible pathophysiological underlying mechanism. However, further studies are required to explore the role of SP, NK1R and trigeminal system in the pathogenesis of SIDS, Sudden intrauterine deaths, still births and sudden deaths later in human life.